2003
DOI: 10.1159/000071710
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Vascular Cell Adhesion Molecules VCAM-1, ICAM-1, and E-Selectin in Dependence on Aging

Abstract: Background: Elevated levels of circulating cell adhesion molecules (cCAMs) such as vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and endothelial leukocyte adhesion molecule-1 (E-selectin) are found in subjects with vascular diseases and in subjects with several risk factors for atherosclerosis. However, data evaluating cCAMs and biological age are limited. Objective: The purpose of this study was to assess in subjects with different cardiovascular risk profiles the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
30
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 25 publications
9
30
1
3
Order By: Relevance
“…Unexpectedly, sVCAM values are higher in the present study than in the previous one. This can be explained because young subjects' usual diet was higher in percentage of energy supplied from fat and did not conform with the fruit and vegetable dietary recommendations compared with the postmenopausal women, as it has been suggested that sVCAM reflects diet more than sICAM [41].…”
Section: Discussionmentioning
confidence: 95%
“…Unexpectedly, sVCAM values are higher in the present study than in the previous one. This can be explained because young subjects' usual diet was higher in percentage of energy supplied from fat and did not conform with the fruit and vegetable dietary recommendations compared with the postmenopausal women, as it has been suggested that sVCAM reflects diet more than sICAM [41].…”
Section: Discussionmentioning
confidence: 95%
“…Surprisingly, increased VCAM-1 expression in the aortic wall with age was not accompanied by an increase in aortic lesions. Studies of human populations also show that circulating VCAM-1 is an age-dependent parameter independent of cardiovascular risk [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Activated endothelial cells elaborate adhesion molecules, cytokines and chemokines, enzymes that synthesize vasoactive molecules (e.g., cyclooxygenase-[COX-]2 and iNOS) and a variety of other gene products. Importantly, phenotypic changes characteristic to endothelial activation (e.g., induction of adhesion molecules, chemokines) have been demonstrated in aging [39][40][41][42]. Also, upregulation of iNOS is present in coronary arteries [18], aorta [23], kidney [43] and other vascular tissues [44] of aged rats.…”
Section: Upregulation Of Vascular Expression Of Inos Cox-2 Chemokinmentioning
confidence: 99%